Writing's on the wall: improving the WHO Surgical Safety Checklist. Issue 1 (15th January 2021) - Cushley, Claire; Knight, Tom; Murray, Helen; Kidd, Lawrence
Abstract : Background and problem: The WHO Surgical Safety Checklist has been shown to improve patient safety as well as improving teamwork and communication in theatres. In 2009, it was made a mandatory requirement for all NHS hospitals in England and Wales. The WHO checklist is intended to be adapted to suit local settings and was modified for use in Gloucestershire Hospitals NHS Foundation Trust. In 2018, it was decided to review the use of the adapted WHO checklist and determine whether improvements in compliance and engagement could be achieved. Aim: The aim was to achieve 90% compliance and engagement with the WHO Surgical Safety Checklist by April 2019. Methods: In April 2018, a prospective observational audit and online survey took place. The results showed compliance for the 'Sign In' section of the checklist was 55% and for the 'Time Out' section was 91%. Engagement by the entire theatre team was measured at 58%. It was proposed to move from a paper checklist to a wall-mounted checklist, to review and refine the items in the checklist and to change the timing of 'Time Out' to ensure it was done immediately prior to knife-to-skin. Results: Following its introduction in September 2018, the new wall-mounted checklist was reaudited. Compliance improved to 91% for 'Sign In' and to 94% for 'Time Out'. Engagement by the entire theatre team was achieved 100% of the time. Feedback was collected, adjustments made and the new checklist was rolled out in stages across all theatres. A reaudit in December 2018 showed compliance improved further, to 99% with 'Sign In' and to 100% with 'Time Out'. Engagement was maintained at 100%. Conclusions: The aim of the project was met and exceeded. Since April 2019, the new checklist is being used across all theatres in the Trust.